PWE-233 Single centre comparison of mortality, hospital recorded serious adverse events (SAE) and primary care recorded opportunistic infections (OI) in IBD patients treated with anti-TNF compared to thiopurines alone. (28th May 2012) - Waters, O; Saunders, M; Bulsara, M; Ahmad, T
Abstract : Introduction: The safety profile of anti-TNF therapy in IBD has been examined in previous case series, however these have been in tertiary centres, have not included a control cohort, or review of primary care records. We aimed to review SAE including primary care recorded OI, in patients treated with anti-TNF compared to a thiopurine alone. Methods: We studied two IBD cohorts: Cohort 1—All 212 anti-TNF treated patients between 1999 and 2010. Cohort 2—220 responders to an invitation sent to 365 patients treated with thiopurines only. A review of primary and secondary care records was conducted. A primary care OI was defined as any infection diagnosed or treated in primary care. Statistical analysis was performed using Stata V.12 software. Proportional hazard regression model was used to assess mortality. Other SAE and OI were studied using logistic regression, t-test, and χ 2 with Fishers exact. Results: Cohort 1: 137 (64.5%) CD patients. 170 (80%) received Infliximab (IFX) as their only anti-TNF treatment, 34 (16%) IFX and Adalimumab (ADA) and 8 (4%) ADA only. Cohort 2: 220 patients comprising 88 (40%) CD. The mean age at drug initiation was 35.3 (SD 16.1) yrs in cohort 1, 45.7 (SD 15.9) yrs in cohort 2 (p<0.0001). Median follow-up after drug initiation in cohort 1 was 2.7 years (0–11.0), total 714.9 yrs, in cohort 2 6.4 (0–30.8) yrs, total 1524  yrs. There were 8 (4%) deaths in cohort 1 (1 cardiovascular (CVS), 3 sepsis, 3 solid organ malignancies, 1 haematological malignancy) and 5 (2%) deaths in cohort 2 (2 CVS, 2 sepsis, 1 haematological malignancy). Cohort 1 patients had a higher mortality when corrected for age at diagnosis (HR 3.4 95% CI 1.1 to 10.5) Abstract PWE-233 figure 1 . In cohort 1 there were two cases of demyelination (1 suspected), 1 TB reactivation, 40 in-patient treated infections, 8 malignancies, seven cases of Clostridium difficile and no drug induced lupus. Hospital recorded SAE did not differ between cohorts 1 and 2 and no risk factors were identified. The mean number of primary care recorded OI was 5.8 (SD 5.8) in cohort 1 and 4.5 (SD 4.2) in cohort 2. Conclusion: The age at diagnosis adjusted mortality of IBD patients treat with anti-TNF is significantly greater than patients treated with thiopurines alone. Causality is unclear and may reflect underlying disease severity. Anti-TNF treated patients have similar rates of other SAE and primary care OI compared to patients treated with thiopurines alone. Competing interests: None declared.